ANALISIS PERSEPSI DUKUNGAN ORGANISASI DAN KETERLIBATAN PEGAWAI PADA PRODUKTIVITAS KERJA DENGAN DIMEDIASI KEPUASAN KERJA - Dini Peristiwanti Ningsih; Woro Utari; Indra Prasetyo (JUIMA : JURNAL ILMU MANAJEMEN, 2023)
To describe organizational support, employee involvement, job satisfaction and work productivity of the employees of the Bojonegoro Regency Community and Village Empowerment Service. To test and analyze the effect of organizational support and employee involvement on employee job satisfaction. the effect of job satisfaction, organizational support and employee involvement on employee work productivity, the effect of organizational support and employee involvement on employee work productivity through job satisfaction. This type of research is explanatory, the research approach used is quantitative. The population in this study were all employees in the Department of Community and Village Empowerment of Bojonegoro Regency as many as 34 people. The sample in this study were 25 employees. The sampling technique is census sampling / total sampling. Analysis of the data used in this study is using SEM PLS analysis. Organizational support, employee involvement, job satisfaction, and work productivity are in the high category. Organizational support and employee involvement have a significant effect on employee job satisfaction. Job satisfaction has a significant effect on employee work productivity. Organizational support and employee involvement do not have a significant effect on work productivity. Organizational support has a significant effect on employee work productivity through job satisfaction. Employee involvement does not have a significant effect on employee work productivity through job satisfaction